Improving the Energy Efficiency of Public Utility Buildings in Poland through Thermomodernization and Renewable Energy Sources—A Case Study - Anna Barwińska-Małajowicz; Radosław Pyrek; Krzysztof Szczotka; Jakub Szymiczek; Teresa Piecuch (Energies, 2023)
Economical and efficient use of energy is promoted around the world as a model of conscious care for the environment in which we live. A mere change of habits in the use of energy can reduce its costs by 5% to 15%, and investments in energy-saving technologies can pay for themselves after just a few years. This case study shows how significant steps can be taken in saving energy in the building of public utility buildings through deep thermomodernization using renewable energy sources—compressor heat pumps and photovoltaics. The article presents a comprehensive thermomodernization of a school building made according to Polish regulations. A detailed description of the tested object is given, and the calculation procedure is described. Next, the optimal investment variant and ex post analysis are described. The implementation of these projects significantly improved the energy efficiency of the building and generated final energy savings of 80%, which will significantly reduce the school’s operating costs. Thanks to the applied improvements, it was possible to save 72.30% of thermal energy in the building, which directly translates into lowering the building’s operating costs. The improvement of energy efficiency indicators ranges from 66% for usable energy to almost 85% for non-renewable primary energy. Furthermore, by reducing the demand for energy used in the building by nearly 74%, we see a reduction in CO2 emissions. The methods used were desk research and an extended case study of Poland, a country facing a number of problems related to energy prices during the energy crisis. In this article, we identify the challenges faced by Poland due to its geopolitical situation, and the solutions introduced to the difficult situation in the energy market come in the form of the thermomodernization of buildings. It was on this basis that Poland was selected as a case study.